A multi‐laboratory assessment of lupus anticoagulant assays performed on the ACL TOP 50 family for harmonized testing in a large laboratory network. (1st March 2022) - Favaloro, Emmanuel J.; Mohammed, Soma; Vong, Ronny; Chapman, Kent; Swanepoel, Priscilla; Kershaw, Geoffrey; Cai, Nancy; Just, Sarah; Connelly, Lynne; Brighton, Timothy; Pasalic, Leonardo
Abstract: Introduction: Lupus anticoagulant (LA) testing is commonly performed within hemostasis laboratories, and the ACL TOP 50 family of instruments represent a new "single platform" of hemostasis instrumentation. Our aim was to evaluate these instruments and manufacturer reagents or alternatives for utility in LA testing. Methods: Comparative evaluations of LA testing using newly installed ACL TOPs 550 and 750 as well as comparative assessments with existing "reference, " predominantly Stago, instrumentation, and reagents. Evaluations comprised both dilute Russell viper venom time (dRVVT) and activated partial thromboplastin time (APTT)‐based assays. Establishment of normal reference ranges (NRR). Results: The HemosIL dRVVT‐based assays showed good comparability with the existing Stago reference method (R > 0.9) and could be considered as verified as fit for purpose. A variety of APTT assays was additionally evaluated for LA utility, and we identified from the assessment good utility of a non‐Werfen solution in Hyphen BioMed Cephen reagents. NRR were established based on ≥120 normal individual plasma samples. Conclusion: This evaluation of LA reagents on ACL TOP 50 Family instruments identified overall acceptable performance of both dRVVT (Werfen solution) and APTT (non‐Werfen solution) to enable harmonization of LA testing in our large network.